Ecological Environmentalism in Geg Ary Suharsani's Kunang-Kunang Hitam (NOBEL: Journal of Literature and Language Teaching, 2023)
The Tamblingan land conflict is closely related to the investment trend heading towards Bali’s upstream area. Investors are converting Tamblingan forest land into hotels and tourism to reap the benefits of nature tourism in the most natural forest. This issue is discussed in the novel Kunang-Kunang Hitam by Geg Ary Suharsani. This paper aims to describe the struggle of the female character Ni Luh Candri in the Tamblingan land conflict as narrated in the novel Kunang-Kunang Hitam (KKH). This study uses a Susan Griffin perspective ecofeminism approach. The results of this study indicate that the struggle of the female character Ni Luh Candri in defending the Tamblingan forest is divided into two forms: Ni Luh Candri’s struggles related to nature, such as refusing land conversion, protecting rare plants, symbolic communication to fireflies and Ni Luh Candri’s struggles related to nature humanistic environment, such as becoming Leak, burning incense, displaying rangda mask, and advocating for communities around the forest. This research proves that women can take various important actions (ecological environmentalism) to preserve the environment.